2009
DOI: 10.1088/0960-1317/19/2/025002
|View full text |Cite
|
Sign up to set email alerts
|

Self-aligned hemispherical formation of microlenses from colloidal droplets on heterogeneous surfaces

Abstract: This paper proposes a drop-on-demand (DOD) theory and scheme for constructing hemispherical refractive microlenses onto underlying heterogeneous (laterally structured) surfaces that consist of hydrophilic s-domains and hydrophobic p-domains. In theory, the drops would self-align themselves into the s-domains by repelling the p-domains due to surface tension, precisely determining the placement though disobeying the Young–Laplace equation. Using a droplet generator (inkjet printhead), in our experiments, evapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…For example, as demonstrated in Figure 3(b), pure water droplets spontaneously formed (self-assembled) the circular and stripe shapes on hydrophilic (glass) domains only of the structured surfaces, on which the glass were pre-patterned with hydrophobic (Teflon) domain by photolithography. Based on this concept of self-assembly on structured surfaces, stable solid formations of droplet deposition for striped channel (Chen et al, 2007) and circular shapes (Chen et al, 2009) were experimentally realized by inkjet printing of colloidal inks. …”
Section: Substrate Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, as demonstrated in Figure 3(b), pure water droplets spontaneously formed (self-assembled) the circular and stripe shapes on hydrophilic (glass) domains only of the structured surfaces, on which the glass were pre-patterned with hydrophobic (Teflon) domain by photolithography. Based on this concept of self-assembly on structured surfaces, stable solid formations of droplet deposition for striped channel (Chen et al, 2007) and circular shapes (Chen et al, 2009) were experimentally realized by inkjet printing of colloidal inks. …”
Section: Substrate Propertiesmentioning
confidence: 99%
“…Some research efforts to avoid the non-uniform droplet deposit were recently reported (Chang et al, 2004;Chen et al, 2004;Weon & Je, 2010), since the deposit thickness is important for many applications such as biochips, LCD color filters, and light-emitting displays. Among them, special treatment on either homogeneous or heterogeneous surfaces plays a critical role on controlling the final deposit formations during evaporation, because of pinning or de-pinning condition as boundary constraints (Chen et al, 2009). …”
Section: Evaporation Depositmentioning
confidence: 99%
See 1 more Smart Citation
“…As a solution, drop-on-demand (DOD) IJP of polymers as a fast prototyping method allows maskless fabrication of various shapes [20], among which hemispherical structures with enhanced profile. Confining the ink either by adjusting the surface energy or topographically by edge confinement enables targeting specific aspect ratios and high thicknesses [21][22][23]. Technically, confining a liquid drop by pinning its contact line on a convex edge can be done with edges whose minimum heights are as low as the length range of the polymer chain [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the microfluidic scheme can be considered to be droplet vaporization deposition (DVD) at low temperature (less than 100 • C), significantly differing from the conventional hightemperature PVD and CVD processes, and also possesses additional precise-patterning ability to various shaping in single step without etching process involved [25], [26]. Based on a DVD process, the varying size hemispherical lenses of simplest circular footprints have been fabricated on either homogeneous [27] or heterogeneous [28] surfaces in our previous studies, demonstrating the self-formation and shaping controllability of droplets by surface tension. With small open cavities rather than flat surfaces with special treatment, the various microstructures in polygonal footprints [29] can be formed and released during droplet evaporation exhibiting drastic change of morphological surfaces from previous ones [27], [28].…”
mentioning
confidence: 99%